OPPORTUNITIES OF CREATIVE IMAGINATION DEVELOPMENT IN ELEMENTARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2023)
This article reflects on the opportunities of Primary School students to develop their creative imagination as well as their creative abilities in the educational process. Scientific and practical recommendations are given on the socio-psychological characteristics of the development of their creative abilities, the use of didactic methods and techniques.